Pediatric phase I trial of oral sorafenib and topotecan in refractory or recurrent pediatric solid malignancies. (29th December 2015) - Reed, Damon R.; Mascarenhas, Leo; Manning, Kathleen; Hale, Gregory A.; Goldberg, John; Gill, Jonathan; Sandler, Eric; Isakoff, Michael S.; Smith, Tiffany; Caracciolo, Jamie; Lush, Richard M.; Juan, Tzu‐Hua; et al.
Abstract : We completed a phase I trial of the combination of sorafenib and topotecan in pediatric patients. We found the combination to have similar pharmacokinetic exposure when compared to the single agent studies and all therapy was delivered by mouth. No objective responses were seen in the patients enrolled. Abstract: Targeted kinase inhibitors and camptothecins have shown preclinical and clinical activity in several cancers. This trial evaluated the maximum tolerated dose (MTD) and dose‐limiting toxicities of sorafenib and topotecan administered orally in pediatric patients with relapsed solid tumors. Sorafenib was administered twice daily and topotecan once daily on days 1–5 and 8–12 of each 28‐day course. The study utilized a standard 3 + 3 dose escalation design. Three dose levels (DL) were evaluated: (1) sorafenib 150 mg/m 2 and topotecan 1 mg/m 2 ; (2) sorafenib 150 mg/m 2 and topotecan 1.4 mg/m 2 ; and (3) sorafenib 200 mg/m 2 and topotecan 1.4 mg/m 2 . Pharmacokinetics were ascertained and treatment response assessed. Thirteen patients were enrolled. DL2 was the determined MTD. Grade 4 thrombocytopenia delaying therapy for >7 days was observed in one of six patients on DL2, and grade 4 neutropenia that delayed therapy in two of three patients on DL3. A patient with preexisting cardiac failure controlled with medication developed a transient drop in the left ventricular ejection fraction that improved when sorafenib was withheld. Sorafenib exposure with or without topotecan was comparable, and the concentration‐time profiles for topotecan alone and in combination with sorafenib were similar. One objective response was noted in a patient with fibromatosis. We determined MTD to be sorafenib 150 mg/m 2 twice daily orally on days 1–28 combined with topotecan 1.4 mg/m 2 once daily on days 1–5 and 8–12. While these doses are 1 DL below the MTD of the agents individually, pharmacokinetic studies suggested adequate drug exposure without drug interactions. The combination had limited activity in the population studied.